Antitumor metabolites of Polygonaceae Juss. family plants (Experimental biology, 2016)
Results of studying of antitumor activity of various structural types of the natural flavonoids (leukoantocyanins, chalcones, flavonols, flavons, flavanons, catechins) extracted with authors from the Polygonaceae Juss. family plants, having industrial quantities in the territory of the Republic of Kazakhstan are given in article. Results of comparative studying of antitumor activity of natural flavonoids of various structural groups and their synthetic derivatives are for the first time presented. Possible mechanisms of anti-proliferative and cytotoxic action of flavonoids are proved.
Keywords: Polygonaceae Juss.; antitumor activity; cytotoxicity; secondary metabolites; polyphenols; flavonoids.